2001
DOI: 10.1111/j.1476-4431.2001.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Upper Airway Obstruction Due to Inflammatory Laryngeal Disease in 5 Cats

Abstract: Objective: To describe a clinical syndrome of upper airway obstruction in 5 cats due to inflammatory laryngeal disease. Series Summary: Medical records of 5 cats with upper airway obstruction and a histopathologic diagnosis of inflammatory laryngeal disease were reviewed. Historical findings included: dyspnea, anorexia, voice change, and gagging/non‐productive retching. Thoracic radiographs revealed a bronchial pattern in 2 cats, with consolidation of the right middle lung lobe in one cats. Laryngeal examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
(19 reference statements)
0
23
0
4
Order By: Relevance
“…In a study 15 of alterations of the tracheal mucosa in dogs that underwent tracheostomy, it was found that the tracheal mucosa had adapted in most dogs by 8 weeks after surgery and had returned to a relatively normal histologic appearance by 16 weeks after surgery. In addition, ILD has previously been attributed to endotracheal intubation in cats, 8 and 1 cat in the present study had undergone endotracheal intubation for dental extraction shortly before signs of respiratory tract disease had first been noticed. When crusting and thick secretions are evident during the immediate postoperative period, nebulization may be required as frequently as every 2 to 4 hours.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…In a study 15 of alterations of the tracheal mucosa in dogs that underwent tracheostomy, it was found that the tracheal mucosa had adapted in most dogs by 8 weeks after surgery and had returned to a relatively normal histologic appearance by 16 weeks after surgery. In addition, ILD has previously been attributed to endotracheal intubation in cats, 8 and 1 cat in the present study had undergone endotracheal intubation for dental extraction shortly before signs of respiratory tract disease had first been noticed. When crusting and thick secretions are evident during the immediate postoperative period, nebulization may be required as frequently as every 2 to 4 hours.…”
Section: Discussionmentioning
confidence: 50%
“…9,13,14 In human patients, humidification is routinely used as a method to reduce tenacity of mucous secretions, with the method and frequency of humidification tailored to individual patient need. Underlying causes of these disease processes in cats have been identified, 7,8,16 and it is likely that multiple factors contribute to these conditions. Thus, it appears that humidification is required most frequently during the first 3 months after surgery and less frequently thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A coagulopathy should be ruled out before performing a tracheostomy. Cats develop laryngeal disease much less commonly than dogs, but inflammatory conditions such as granulomatous laryngitis (Costello and others 2001), and neoplastic processes such as lymphoma, have been reported. Histology is required for a definitive diagnosis as gross appearance is unreliable.…”
Section: Upper Airway Diseasementioning
confidence: 99%